Enterprise boundaries in the area of human resources - Piwowar-Sulej, Katarzyna; Bąk-Grabowska, Dominika (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
Purpose – The study attempts to operationalize the concept of organizational boundaries in terms of human resources. The purpose of the study is to identify the scope, the place of enterprise boundaries’ occurrence and their nature in situations when alternative solutions are applied with reference to employment. It was accompanied by specifying the nature of psychological contract. Design/methodology/approach – Case study methodology was applied. Findings – The empirical research confirmed that formal boundaries are different from the real ones related to the functioning of people employed in a particular entity, performing work for the benefit of this entity and being subject to the processes of HRM. Objective boundaries are not the same as the subjective ones referring to the perception of boundaries and the attachment identified by the providers of contacted tasks. The majority of the analysed psychological contracts were of a temporary nature. Originality/value – The notion of a particular conceptual framework (recognized and shared in the scientific environment) allows for the comparison of research results and the development of theories. The methodology for analysing organizational boundaries in human resources (OBHR) was proposed. The presented results of empirical studies provide knowledge about the existence and perception of OBHR referring to non-standard employment forms as well as work organization based on project teams allowing for analytical generalizations. The presented discussion can also become the foundation for developing quantitative research the results of which could facilitate statistical generalizations.
Argumenta Oeconomica, 2018, Nr 2 (41), s. 357-388
Keywords: organizational boundaries; human resource management